The impact of COVID-19 on the training of oral maxillofacial surgeons (Research, Society and Development, 2023)
Dental surgeons with oral and maxillofacial specialties are trained in a hospital setting, a requirement of the qualification process in the area. However, with the emergence of COVID-19 and the speed of its spread, various activities in society were interrupted. Such a fact reverberated in professional training. This study aimed to analyze the perception of oral and maxillofacial surgery residents about the impact of COVID-19 on their training. Research with a qualitative approach had, as a scenario, four hospitals with residencies in oral and maxillofacial surgery in Fortaleza, Ceará, Brazil. Sixteen residents were interviewed in the second half of 2020 by a trained researcher using a semi-structured questionnaire about the impact of COVID-19 on the training process, perceived gaps, attitudinal changes, and psychosocial repercussions. The interviewer recorded and transcribed the interviews. Later, the content was investigated based on the assumptions of the theory of bounded rationality. After the reading process, four analytical categories emerged: changes in daily life, biosecurity and health protocols, social and psychological impacts, and agreement in managerial attitudes. Despite the dissatisfaction, given the complex and uncertain scenario, virtualization was the only casual alternative to avoid a more considerable effect on training. In the residents' perception, there was a significant loss of activities that harmed the technical and psychological aspects, requiring management monitoring to fill this gap in training.